RAGAM IRONI DALAM NOVEL KARYA IKA NATASSA “CRITICAL ELEVEN” - Sholihatun, Prima; Muliyadi, Muliyadi (Jurnal Komposisi, 2023)
This study aims to analyze the use of irony in the novel "Critical Eleven" by Ika Natassa using a semantic approach. Irony is a form of indirect language, used when the speaker or writer expresses one thing, but implies another (Grice, 1975). Irony is a literary device often used in novels to create an additional dimension to the narrative. In the context of the novel by Ika Natassa, irony is present as a strong element in conveying messages and arousing the minds of readers. In this analysis, the researcher identifies and analyzes various examples of irony that are present in the novel. The semantic approach helps in understanding the shift in the meaning of words or phrases used by the author to create irony in the story. Through a semantic approach, the investigator hides the contrast between the literal meaning and the actual meaning intended in this novel. Our semantic analysis includes an understanding of how irony is used to convey conflicting messages, create humorous effects, or convey social criticism. The results of our analysis reveal that irony in "Critical Eleven" provides a strong dimension in shaping the reader's understanding of the characters, conflicts, and themes in this novel. Irony exists as an effective means of arousing feelings, generating reflection, and providing a different perspective in reading and analyzing literary works.